Tittle:A Retrospective Cohort Study Of Incidence Of Postherpetic Neuralgia In Patients More Than 50 Years Of Age In A Suburban Hospital - Dr Siri, Resident, Prof.Jayakar Thomas (Drugs and Cell Therapies in Hematology, 2021)
OBJECTIVE:Postherpetic neuralgia (PHN) is a common clinical complication of HZ characterised by severe, often persistent, pain after the rash has been resolved[1]. METHODS:Patients aged more than 50years of age who presented with PHN were considered who visited Chettinad Hospital and Research Institute ,Kelambakkam between Jan2021-July2021.Their complete history were collected and evaluated RESULTS:A total of 70 patients presented with Herpes zoster out of which the incidence of PHN was 75.71%(53) in patients aged >50years,which increased with age;the incidence being highest in >80years of age(41.5%)and also increased incidence in patients with comorbidities (hypertension, diabetes mellitus,patients on immunosuppressive therapy) CONCLUSION:Incidence of PHN increases with age, association with comorbidities,with increased prodromal symptoms,untreated patients and interferes with daily life activities